Perancangan dan Pengelolaan Sistem Informasi Desa (SID) Bagi Aparat Desa Puasana Kecamatan Moramo Utara Kabupaten Konawe Selatan - Laome, Lilis; Zamrun F, Muh.; Variani, Viska Inda; Mukhsar, Mukhsar; Tenriawaru, Andi (Vokasi Universitas Halu Oleo, 2019)
The progress of information technology is rapidly increasing, making it easy for everyone to access information quickly, including the Puasana villagers in getting information from the village government. Information technology also makes it easy for village officials to collect data on all village potentials in a village information system (SID). The existence of this system can also provide an overview of the potential of the village for the wider community, so that it can open economic opportunities to improve people's lives. Puasana Village, is one of the villages that have a variety of natural resource potentials that needs to be published continuously. A qualified village apparatus in the field of information technology is needed so that this effort can be realized. Therefore, assistance is needed to Puasana village officials to be able to operate SID so that they can update their village information at any time. In addition, this SID can also facilitate the village administration process because it is no longer done manually. Well-organized and good information will make it easier for people to get the information they want. Based on the results of the mentoring shows that with the availability of SID the community can easily access village information through online and offline. Village officials also gained additional knowledge related to making SID and could update the village profile at any time